Legal Protection for People with Mental Disorders (ODGJ) as Victims of Rape Resulting in Pregnancy - Rahmadiani Kartika Lestari; Samsul Arifin (Universitas Merdeka Madiun, 2026)
Introduction to the Problem: Sexual violence against people with mental disorders (ODGJ) creates double vulnerability, with victims facing the trauma of rape and limited access to justice. This issue is exacerbated by the resulting pregnancy, and even worse, the birth of a child from the crime. Purpose/Study Objectives: From this problem, this study aims to understand the legal protection for people with mental disorders (ODGJ) who become pregnant as a result of the crime of rape. Design/Methodology/Approach: The research method used in this study is Empirical Legal Research with a qualitative approach, with data collection techniques through in-depth interviews. Findings: The results of this study conclude that legal protection for people with mental disorders (ODGJ) who are victims of rape resulting in pregnancy is currently inadequate and faces gaps in implementation in the field. ODGJ are doubly vulnerable due to stigma and mental health conditions that hinder their ability to resist, report, and access justice. Ideal protection should be comprehensive and non-discriminatory, and provide ongoing psychological rehabilitation to address multiple traumas. Furthermore, if the pregnancy continues to childbirth, the focus of legal protection must shift entirely to guaranteeing the rights to life, growth, and development of the child born from the crime. Paper Type: Research Article